Information creativity as a right in the new society - Aydin Rzayeva, Gulnaz (Vilnius University Open Series, 2020)
Formation of e-governance has resulted in the leading role of information in the digital society. Thus, the main feature of the information society is the participation of all members of the society in the interchange of information. Therefore, information creativity has become a subject of discussion as a modern form of freedom of artistic creativity. Of course, this is not about simple information, but rather the creation of knowledge, which is the most superior form of information. Such information creativity makes necessary to regulate intellectual property issues and restrictions on information creativity. In the article werer analyzed these issues and were put forward suggestions and recommendations.